Superior Long‐Term Outcomes of Adult Living Donor Liver Transplantation: A Cumulative Single‐Center Cohort Study With 20 Years of Follow‐Up. Issue 5 (1st February 2022) - Goto, Toru; Ivanics, Tommy; Cattral, Mark S.; Reichman, Trevor; Ghanekar, Anand; Sapisochin, Gonzalo; McGilvray, Ian D.; Sayed, Blayne; Lilly, Les; Bhat, Mamatha; Selzner, Markus; Selzner, Nazia
Abstract : Living donor liver transplantation (LDLT) is an attractive alternative to deceased donor liver transplantation (DDLT). Although both modalities have similar short‐term outcomes, long‐term outcomes are not well studied. We compared the 20‐year outcomes of 668 adults who received LDLT with1596 DDLTs at the largest liver transplantation (LT) program in Canada. Recipients of LDLT were significantly younger and more often male than DDLT recipients ( P < 0.001). Autoimmune diseases were more frequent in LDLT, whereas viral hepatitis and alcohol‐related liver disease were more frequent in DDLT. LDLT recipients had lower Model for End‐Stage Liver Disease scores ( P = 0.008), spent less time on the waiting list ( P < 0.001), and were less often inpatients at the time of LT ( P < 0.001). In a nonadjusted analysis, 1‐year, 10‐year, and 20‐year patient survival rates were significantly higher in LDLT (93%, 74%, and 56%, respectively) versus DDLT (91%, 67%, and 46%, respectively; log‐rank P = 0.02) as were graft survival rates LDLT (91%, 67%, and 50%, respectively) versus (90%, 65%, and 44.3%, respectively, for DDLT; log‐rank P = 0.31). After multivariable adjustment, LDLT and DDLT were associated with a similar hazard of patient and graft survival. Our data of 20 years of follow‐up of LDLT from a single, large Western center demonstrates excellent long‐term outcomes for recipients of LDLT.